Agricultural land use impacts on aquatic macroinvertebrates in small streams from La Vieja river (Valle del Cauca, Colombia) - Giraldo, Lina Paola; Chará, Julián; Zuñiga, María del Carmen; Chará-Sema, Ana Marcela; Pedraza, Gloria (Revista de Biología Tropical, 2014)
The expansion of the agricultural frontier in Colombia has exerted significant pressure on its aquatic ecosystems during the last few decades. In order to determine the impacts of different agricultural land uses on the biotic and abiotic characteristics of first and second order streams of La Vieja river watershed, we evaluated 21 streams located between 1 060 and 1 534 m asl in the municipalities of Alcalá, Ulloa, and Cartago (Valle del Cauca, Colombia). Seven streams were protected by native vegetation buffers, eight had influence of coffee and plantain crops, and six were influenced by cattle ranching. Habitat conditions, channel dimensions, water quality, and aquatic macroinvertebrates were studied in each stream. Streams draining cattle ranching areas had significantly higher dissolved solids, higher phosphorus, higher alkalinity, higher conductivity, and lower dissolved oxygen than those covered by cropland and forests. Coarse substrates and diversity of flow regimes were significantly higher in cropland and protected streams when compared to streams affected by cattle ranching, whereas the percent of silt and slow currents was significantly higher in the latter. A total of 26 777 macroinvertebrates belonging to 17 orders, 72 families and 95 genera were collected. The most abundant groups were Diptera 62.8%, (Chironomidae 49.6%, Ceratopogonidae 6.7%), Mollusca 18.8% (Hydrobiidae 7.2%, Sphaeriidae 9.6%) and Trichoptera 5.7% (Hydropsychidae 3.7%). The Ephemeroptera, Trichoptera, and Plecoptera orders, known for their low tolerance to habitat perturbation, had high abundance in cropland and forested streams, whereas Diptera and Mollusca were more abundant in those impacted by cattle ranching. Results indicate that streams draining forests and croplands have better physical and biological conditions than those draining pastures, and highlight the need to implement protective measures to restore the latter. Rev. Biol. Trop. 62 (Suppl. 2): 203-219. Epub 2014 April 01.